A review of the management of anterior open bite malocclusion - Lawry Denise M.; Heggie Andrew A.C; Crawford Edward C.; Kevin Ruljancich M. (Sciendo, 1990)
Anterior openbite (AOB) malocclusion is considered one of the most demanding challenges for the orthodontist, as occlusal correction is difficult, facial aesthetics may be unsatisfactory and the incidence of relapse is high.